Prediction of Heart Disease Using AI and NLP Techniques - Sabeena, S; Sujitha, V (International Journal of Computer Sciences and Engineering, 2025)
The leading cause of death in recent days due to heart diseases for both men and women. When the heart is too weak to pump blood throughout the body, heart failure occurs. The heart attack happens suddenly when there is a total blockage of an artery which supplies the blood to the heart. The chances of survival after the attack happen to a person is very low and most cases death will be an ultimate result if exact first step measures are not taken immediately. Most of the people who are in heart failure die within five years of diagnosis. Thus, we had proposed AI techniques to analyze the patient information in this paper including natural language processing methods to obtain accuracy in prediction. We used AI and NLP techniques in which decision tree algorithm is used to extract information from unstructured data such as doctor’s notes by analyzing the information and data that includes risk criteria or other types of symptoms. The aim of this paper is to predict whether a patient is likely to affect heart disease or not in early. This intelligent system decides the line of treatment to be followed by suitable databases obtained.